Duration of regional unemployment spells in Slovenia - Boršič, Darja (Managing global transitions, 2009)
The paper begins with an overview of the unemployment rate in Slovenia and focuses on duration of unemployment and regional characteristics of the unemployment rates. It is shown that the dispersion of regional unemployment rate is gradually decreasing and is also slightly below European average on NUTS 3 level. The analysis of the duration of regional unemployment spells is based on the data obtained from the Employment Office of the Republic of Slovenia, which consists of the unemployment spells between January 1st, 2002 and November 18th, 2005 with more than 450,000 entries. The Kaplan - Meier estimates of the survival function are presented and the effects of region on the duration of unemployment spells are discussed.
Keywords: trg dela; trg delovne sile; unemployment; brezposelnost; ekonomski modeli; ekonomske analize; Slovenia; Slovenija